PENGUATAN SIKAP MENTAL KEWIRAUSAHAAN PENGRAJIN TAS BERBAHAN LIMBAH PLASTIK KEMASAN MINUMAN DI WILAYAH EKS ZONA MERAH PANDEMI COVID-19 KOTA SEMARANG - Iriyanto Widisuseno; Sri Sudarsih (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2023)
In reality the success of a businessman does not start with sufficient capital, but begins with the readiness of a strong entrepreneurial mentality. In the city of Semarang there are many home industry craftsmen, ranging from culinary, tourism to crafts. One of them, in the Sendangmulyo Village area, is a group of affected communities who started a bag craftsman business made from plastic waste packaging for drinks. This group of craftsmen is still prone to failure due to mental factors. This community service activity aims to strengthening the entrepreneurial mentality of bag craftsmen of entrepreneurs making bags made from plastic waste, so that they are more independent, confident in facing competition, adapting to change, not giving up easily. How to strengthen using debriefing methods, training, field visits. The results of this service activity are expected in the future development process to make bag craftsmen able to survive and develop their production independently and expand the market. In addition, assisting the government in advancing MSMEs as the backbone of regional economic strength.Keywords: Strengthening, mental attitude, waste bag craftsmen, able to face competition, survive, expand market.